Obesity negatively impacts outcome in elderly female patients with aggressive B-cell lymphomas treated with R-CHOP: results from prospective trials of the German high grade non-Hodgkin's lymphoma trial group. - Hohloch, K.; Altmann, B.; Pfreundschuh, M.; Loeffler, M.; Schmitz, N.; Zettl, F.; Ziepert, M.; Trumper, L. (Br J Haematol, 2018)
To study if obesity is a risk factor in elderly patients (>60 years) with aggressive B-cell lymphoma, the outcomes of 576 elderly patients treated with rituximab in the RICOVER-60 trial were analysed in a retrospective study with regard to body mass index (BMI) and gender. Of the 576 patients, 1% had low body weight (BMI < 18.5), 38% were normal weight (18.5 </= BMI < 25), 42% were overweight (25 </= BMI < 30) and 19% were obese (BMI >/= 30). Event-free (EFS), progression-free (PFS) and overall survival (OS) according to BMI showed no significant differences for all and for male patients. EFS (P = 0.041), PFS (P = 0.038) and OS (P = 0.031) were significantly better for female non-obese patients. A multivariate analysis adjusted for International Prognostic Index risk factors confirmed these results, with the following hazard ratios (HR) for obesity (BMI >/= 30) for EFS/PFS/OS: all patients - 1.4/1.4/1.4 (not significant); male patients - 1.2/1.2/1.0 (not significant) and female patients - 1.7 (P = 0.032)/1.9 (P = 0.022)/2.0 (P = 0.017). In conclusion, obesity is a risk factor that influences treatment outcome in elderly female patients with aggressive B-cell lymphoma treated with R-CHOP (rituximab + cyclophosphamide, doxorubicin, vincristine, prednisolone). The inferior outcomes in obese female patients may be due to faster rituximab clearance in obese females.
Keywords: Age Factors; Aged; Aged, 80 and over; Antibodies, Monoclonal, Murine-Derived/adverse effects/therapeutic use; Antineoplastic Combined Chemotherapy Protocols/adverse effects/therapeutic use; Body Mass Index; Cyclophosphamide/adverse effects/therapeutic use; Disease Progression; Doxorubicin/adverse effects/therapeutic use; Female; Germany; Humans; Lymphoma, B-Cell/*complications/drug therapy/*mortality/pathology; Male; Middle Aged; Neoplasm Grading; Neoplasm Staging; Obesity/*complications; Prednisone/adverse effects/therapeutic use; Rituximab; Sex Factors; Survival Analysis; Treatment Outcome; Vincristine/adverse effects/therapeutic use